F28. CLINICAL VALIDATION OF THE GLASGOW ANTIPSYCHOTIC SIDE EFFECT SCALE (GASS). (9th April 2019) - Bock, Marlene S; van Achter, Oona N; Dines, David; Correll, Christoph U; Mors, Ole; Østergaard, Søren D; Kølbæk, Pernille
Abstract: Background: Antipsychotics are the mainstay in the treatment of schizophrenia and other psychotic disorders. Treatment with antipsychotics is associated with significant side effects, including weight gain, sedation and parkinsonism. These side effects may reduce the quality of life and result in poor treatment adherence. Therefore, regular screening and monitoring of side effects is essential to ensure optimal treatment adjustment and outcomes. The UKU side effect scale (UKU) is the most comprehensive tool used to assess multi-domain side effects. This scale is administered by trained health care professionals based on a long semi-structured interview that precludes its widespread clinical use. In order to implement routine side effect screening and monitoring in real-world settings, a less time-consuming rating scale is needed. The Glasgow Antipsychotic Side Effect Scale (GASS) is a patient self-report scale developed exactly for this purpose. Until now, GASS has only been validated using other self-report side-effect rating scales as the reference, which is suboptimal from a validation perspective. Therefore, the aim of the present study was to perform a clinical validation of the GASS using the health care professional-administered UKU assessment as the gold standard reference. Methods: Participants must be ≥18 years old, have a diagnosis of a psychotic disorder (ICD-10: F2x.x) and receive treatment with an antipsychotic at the outpatient clinic, Department for Psychosis, Aarhus University Hospital, Denmark. Each participant will self-rate his/her side effects on the GASS. Additionally, the participants will fill in the 5-item World Health Organization well-being index (WHO-5). Subsequently, one of three trained raters will conduct the UKU interview and rate the participant's side effects. The scores on the GASS items will be compared with the scores on the corresponding items on the UKU. The statistical analyses will include calculation of specificity, sensitivity, positive predicative value, and negative predictive value of the GASS as well as the intraclass correlation coefficient. Results: Preliminary results of the study: Altogether 81 antipsychotic-treated outpatients with schizophrenia-spectrum disorders (age= 42.3±13.4 years, males=43.3%, schizophrenia=76.5%) completed the GASS and were subsequently rated on the UKU-SERS-Clin by a trained rater. Statistical analysis showed satisfactory values with sensitivity values >75%, specificity values >70% and NPV >79% for the majority of GASS items. Time to complete all items of the GASS (n = 57 with complete data) was 3.8 (± 2) minutes. Further, the GASS total score was negatively correlated with the WHO-5 total score. The full results of the study will be presented at the SIRS 2019 conference. Discussion: The GASS was shown to have acceptable properties for a self-rated side effect screening tool and can be implemented in clinical practice to aide measurement-based care and decision-making.